ANALISIS KEKUATAN MASSA BATUAN ANDESIT MENGGUNAKAN KAIDAH KRITERIA KERUNTUHAN HOEK-BROWN UNTUK MENGETAHUI NILAI FAKTOR KEAMANAN LERENG PADA DAERAH SELOHARJO, KECAMATAN PUNDONG, KABUPATEN BANTUL, DIY - Nur Widi Astanto Agus Tri Heriyadi; Dina Tania (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
The study area has a steep hill morphology with dominant lithology of andesite lava from the Ngelanggran Formation. Steep morphology with water saturated conditions and platy joints on andesite lava as rock discontinuities with different properties and weathering can be weaking the slope stability. Analysis of the rock mass strength of andesite lava with Hoek-Brown collapse criteria using GSI, mi, uniaxial compressive strength, and D values ​​can be used to obtain rock strength in the form of cohesion (c) and internal friction angle (ɸ), to be applied in the analysis of slope stability. The safety factor (FS) on the slope concists lithology and platy joints and massive using the equilibrium limits approach on the natural slopes shows on safe conditions (FK = 7.5). On very steep slope (slope angle 80o) in LP S09B location which is the former slope of mining activity with lithology andesit platy jointings have strong slopes, and in the field of rock mass movement shows the result of FK value = 1.3 which is below the PU standard (> 1.5). Slope reinforcement can be done by lowering slope angle up to 75o so that the safe conditions at FS = 2.4.